Pandemic Year in The Polish Steel Sector: Steel Production and Apparent Steel Use In 2020 Compared to Previous Year - Bożena GAJDZIK (Communications of International Proceedings, 2021)
The article presents the situation in the Polish steel sector in the pandemic year. The diagnosis of the situation was made on the basis of reporting data. The data were arranged according to the following categories: steel production and apparent steel use. The time scope of analysis covers the year 2020. Data from this year were compared with data from the previous year. Data were analysed in monthly periods. The adopted time interval of the analysis gives a detailed picture of the impact of the pandemic, which appears in Poland in March 2020, on the volume of steel production and its consumption in Poland.
Keywords: Poland; steel industry; steel production; apparent steel use; pandemic period